Crispr/Cas9-Mediated Suppression Of Dual-Specificity Phosphatase 6 (Dusp6) Inhibits Cell Viability, Growth, Survival And Adhesion In Ht-29 Human Colorectal Cancer Cell Line - Ahmad, Muhammad Khairi (2024)
Globally, human colorectal adenocarcinoma (CRC) was ranked third and second for the cancer incidence and mortality rate, while in Malaysia, it was ranked second and third for the cancer incidence and mortality rate. Despite its efficacy, the currently available CRC treatment has side effects and complications that compromise the patients’ well-being. Dual-specificity phosphatase 6 (DUSP6), a member of the MAPK phosphatase family, has been identified as pro-oncogenic, tumour-suppressive, or both in many cancers. Nevertheless, its role and significance in the human CRC are poorly studied. Therefore, this research aims to investigate the role and significance of the DUSP6 gene in CRC through modification of its gene expression.